Two kisses for Maddy : a memoir of loss & love - Logelin, Matthew (New York : Grand Central Pub., 2011)
Matt Logelin writes a courageous and searingly honest memoir about the first year of his life following the birth of his daughter and the death of his wife.
Photographs on lining papers.
Keywords: Logelin, Matthew; Logelin, Matthew -- Marriage; Logelin, Matthew -- Family; Single fathers -- United States -- Biography; Widowers -- United States -- Biography; Spouses -- Death -- Psychological aspects -- Case studies; Mothers -- Death -- Psychological aspects -- Case studies; Loss (Psychology) -- Case studies; Infants -- Care -- United States -- Case studies